2012
DOI: 10.1093/toxsci/kfs131
|View full text |Cite
|
Sign up to set email alerts
|

Non-dioxin-like AhR Ligands in a Mouse Peanut Allergy Model

Abstract: Recently, we have shown that AhR activation by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) suppresses sensitization to peanut at least in part by inducing a functional shift toward CD4(+)CD25(+)Foxp3(+) T cells. Next to TCDD, numerous other AhR ligands have been described. In this study, we investigated the effect of three structurally different non-dioxin-like AhR ligands, e.g., 6-formylindolo[3,2-b]carbazole (FICZ), β-naphthoflavone (β-NF), and 6-methyl-1,3,8-trichlorodibenzofuran (6-MCDF), on peanut sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…43 Similarly, two novel antiallergy therapeutics with AhR binding activity suppressed T-cell activation by DCs in mouse models of allergic airways inflammation, 36,44,45 but several non-dioxin AhR ligands failed to inhibit peanut-specific responses in a food allergy model. 26 The relative contribution of AhR ligands to immune regulation via T cells or DCs is also difficult to assess in whole animal models. Herein, we have shown that endogenous AhR ligands contributed to the regulation of lung immune responses via lung DCs, such that AhR À/À DCs, unable to respond to these ligands, exhibited a pro-inflammatory and pro-allergic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Similarly, two novel antiallergy therapeutics with AhR binding activity suppressed T-cell activation by DCs in mouse models of allergic airways inflammation, 36,44,45 but several non-dioxin AhR ligands failed to inhibit peanut-specific responses in a food allergy model. 26 The relative contribution of AhR ligands to immune regulation via T cells or DCs is also difficult to assess in whole animal models. Herein, we have shown that endogenous AhR ligands contributed to the regulation of lung immune responses via lung DCs, such that AhR À/À DCs, unable to respond to these ligands, exhibited a pro-inflammatory and pro-allergic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Interestingly, three different non-dioxin AhR ligands all failed to suppress the allergic response in a mouse model of peanut allergy. 26 As a result, the role of endogenous AhR ligands on immune cell function remains unclear. …”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…We determined hepatic CYP1A1 activity using ethoxyresorufin- O -deethylase (EROD) activity in hepatic microsomal fractions as described by Schulz et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Acrolein is known to block NF-κB signaling similar like its chemical derivative cinnamaldehyde29 via its reactive unsaturated aldehyde by preventing oligomerization of TLR4 on the plasma membrane59. Consequently, we went in search for a possible cytosolic interaction partner for acrolein and found AhR that –with other ligands - has already been associated with suppression of Th2 cell differentiation6061 and increased numbers of CD4+CD25+Foxp3+ cells61 in vivo . Using an AhR- reporter cell line30, we were able to show that acrolein concentration-dependently activated AhR and that activation was antagonised by resveratrol, as well as by the Ahr antagonist 3′-methoxy-4′-nitroflavone.…”
Section: Discussionmentioning
confidence: 99%